Prediction of rowing ergometer performance by technical and core stability parameters - Simon, F. R.; Ertel, G. N.; Duchene, Y.; Maciejewski, H.; Gauchard, G. C.; Mornieux, G. (Journal of Sports Sciences, 2023)
The purpose of this study was to evaluate the influence of technical and core stability parameters on rowing ergometer performance defined as mean power at the handle. Twenty-four high-level rowers were evaluated at their competitive stroke rate on an instrumented RowPerfect 3 ergometer to determine leg, trunk and arm power output, while trunk and pelvis 3D kinematics were measured. Linear mixed models revealed that mean power at the handle was predicted by the power output of legs, trunk and arms (r2 = 0.99), with trunk power being the best predictor. Time to peak power, work ratio and mean to peak power ratio were relevant technical parameters significantly predicting the different segments` power. In addition, a greater trunk range of motion significantly influenced the power produced by this segment. Accordingly, achieving an earlier peak power together with enhanced work production at the trunk and arm levels, as well as distributing the segments power over the whole drive phase, could serve as recommendations for technical training of rowers on dynamic ergometers in order to produce higher power output. Furthermore, the trunk appears to play a major role as a power producer within the kinetic chain from the legs to the arms.